Alkaline Phosphatase Levels Before and After Nonsurgical Periodontal Therapy - Pradhan, Shaili; Koirala, Pramod Kumar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Chronic periodontitis is a multifactorial disease resulting in the inflammation and destruction of the supporting structures. Early detection of periodontal changes, prognosis and efficacy of treatment have been monitored by Alkaline Phosphatase Levels (ALP) levels. Objective: This study was carried out to determine level of ALP in saliva and serum before and after periodontal therapy. Methods: This pretest posttest study included 22 patients with generalised chronic periodontitis (GCP). The patients received nonsurgical periodontal therapy (NSPT). Saliva and serum levels of ALP were measured at baseline and after two months of periodontal therapy. Results: Twenty-two patients of mean age 44 years were analysed. Participants had significantly better periodontal parameters after two months. Salivary ALP levels, which were high at baseline, decreased after periodontal treatment. A significant positive correlation (0.0001) was found between the salivary levels of ALP and periodontal inflammatory conditions. Gingival index was found directly proportional with salivary ALP level but not with serum ALP. Conclusion: Periodontal therapy lowered the levels of ALP saliva in GCP patients with high ALP levels. Biochemical analysis of enzymes found in saliva may help in patients’ evaluation to determine the control and progression of periodontal destruction and aid in a correct diagnosis, prognosis and, consequently, better treatment.